635 Providing Assessment and Treatment for Children at Home (PATCH); better for patients and better for the planet. (17th August 2022) - Rose, Katy; Turner, Joanna; King, Natasha; Corey, Megan; Cleugh, Francesca
Abstract : Aims: Our hospital started PATCH an innovative extension of a 'hospital-at-home' service in 2016. The team is made up of experienced paediatric nurses and aims to reduce short stay admissions and re-attendance at the hospital for moderately unwell children by using phone call reviews and home visits. It also promotes education and confidence in parents to manage common childhood illnesses at home when safe to do so. The team have gone from strength to strength since conception and acts as an inspiring model of care which is now being taken up by numerous other trusts. This piece of work aimed to model how this innovative service model has captured the triple bottom line of sustainable quality improvement; improving care for patients (social costs), remaining econonomically cost efficient and reducing the environmental costs through carbon footprint reduction. 1 Methods: The PATCH service collects monitoring information across core domains to understand 'what would happen if PATCH didn't exits' for each month. Data exists via the Greener NHS archived service the Sustainable development unit which ascribes a carbon footprint cost in kg to key NHS activities. 2 The carbon footprint reduction was mapped to each unit of activity saved The PATCH Team collect data around their transport activity; this was deducted from the carbon savings of activities avoided to try and provide a more balanced view, Results: The figures for this service in a single unit equate to a carbon saving of 2331kgCO2 e ! See table 1 . As the PATCH model expands across the 3 other large local trusts this could save the equivalent carbon of driving a small petrol car from London to Liverpool 126 times. 3 Conclusion: This model of care demonstrated has already proved to be cost effective and received excellent patient feedback 4 but this demonstrates that there are also significant potential carbon savings. We must encourage quality improvement and service innovation strategies to embrace the triple bottom line model to ensure social and environmental sustainability is embedded into the NHS model. References: Sustainability in quality improvement: redefining value. Frances Mortimer et al. Future Healthc J Jun 2018, 5 (2) 88-93. doi:10.7861/futurehosp.5-2-88 Archived via Greener NHS, Sustainable Development Unit. Carbon Hotspots update for the health and care sector in England 2015 . Cambridge: SDU, 2016.Google Scholar Government emission conversion factors for greenhouse gas company reporting: full set 2021. Greenhouse gas reporting: conversion factors 2021 - GOV.UK (www.gov.uk) Piloting patch – providing assessment and treatment for children at home – and piecing together what works Ward C, Knight K, Ballard M, et al. Emergency Medicine Journal 2017;34: A895-A897.